Until the fires stopped burning 9/11 and New York City in the words and experiences of survivors and witnesses - Strozier, Charles B. (Columbia University Press, 2011)
Collects interviews with survivors, bystanders, and emergency workers during the September 11 terrorist attack on the World Trade Center, focusing on the different "zones of sadness" affected by the attack.